2004
DOI: 10.3201/eid1002.030730
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for SARS among Persons without Known Contact with SARS Patients, Beijing, China

Abstract: Most cases of severe acute respiratory syndrome (SARS) have occurred in close contacts of SARS patients. However, in Beijing, a large proportion of SARS cases occurred in persons without such contact. We conducted a case-control study in Beijing that compared exposures of 94 unlinked, probable SARS patients with those of 281 community-based controls matched for age group and sex. Case-patients were more likely than controls to have chronic medical conditions or to have visited fever clinics (clinics at which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
201
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(211 citation statements)
references
References 13 publications
2
201
0
8
Order By: Relevance
“…According to our analysis, use of surgical masks by the exposed persons was associated with a lower risk of nosocomial acquisition of S-OIV, which was consistent with previous studies suggesting that wearing a surgical mask might decrease the risk of SARS infection. 7 This measure discouraged the use of fingers to touch the mucous membranes of the nostrils and mouth since such spontaneous behaviour was not infrequently observed. 8 Wearing surgical masks by the index persons as a form of source control also reduced the risk of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…According to our analysis, use of surgical masks by the exposed persons was associated with a lower risk of nosocomial acquisition of S-OIV, which was consistent with previous studies suggesting that wearing a surgical mask might decrease the risk of SARS infection. 7 This measure discouraged the use of fingers to touch the mucous membranes of the nostrils and mouth since such spontaneous behaviour was not infrequently observed. 8 Wearing surgical masks by the index persons as a form of source control also reduced the risk of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Although human-to-human transmission of SARS-CoV is less efficient than for other air-borne viruses such as influenza A viruses, the recent SARS epidemic was characterised by several explosive outbreaks [4,24]. Most infections resulted from direct transmission via respiratory droplets during close personal contact and adequate protective measures were shown to be effective [22,25]. However, there are a number of instances when transmission occurred through other modes not yet well defined.…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study in Hong Kong (Lau et al, 2004) found a very similar effectiveness of handwashing >10 times a day in the community in preventing the transmission of SARS (OR = 0.58). Another case-control study in Beijing (Wu et al, 2004) found that handwashing after returning home had a protective effect (OR = 0.3). More recently, a meta-analysis of 6 casecontrol studies (Jefferson et al, 2008), found that handwashing > 10 times daily was remarkably effective in preventing SARS (OR = 0.45, CI 0.36-0.57).…”
Section: Discussionmentioning
confidence: 99%